Evidence upon oath touching the condition and treatment of the Negro population of the British West India colonies (Slavery tracts & pamphlets from the West India Committee collection, 1833)
Extracts from the Minutes of evidence, compiled on behalf of the "colonists" to counteract the effect of selections published by "the active party opposed to the colonists."